Knowledge entrepreneur exploring the model in Malaysian organizational context - Ahmad Abdul Rahman, Yeop Yunus Nek Kamal (N/A, 2014)
Knowledge entrepreneur exploring the model in Malaysian organizational context by Ahmad Abdul Rahman, Yeop Yunus Nek Kamal,